LIKE CHEBYSHEV’S INEQUALITIES FOR CONVEX FUNCTIONS AND APPLICATIONS - Belaıdi, Benharrat; Latreuch, Zinelâabidine (Acta Universitatis Apulensis, 2013)
In this paper, we will show some new inequalities for convex functions, and we will also make a connection between them and Chebyshev’s inequality, which implies the existence of new class of functions satisfying Chebyshev’s inequality.
Keywords: Chebyshev's inequality; Convex functions; Symmetric functions